2023
DOI: 10.3389/fonc.2023.1221309
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic cavernous hemangioma developed in non-small cell lung cancer patients after receiving Camrelizumab treatment: two case reports

Abstract: PurposeTo report two cases of hepatic cavernous hemangioma, a rare complication, in patients with locally advanced and advanced non-squamous non-small cell lung cancer (NSCLC) treated with PD-1 inhibitors. Additionally, to share clinical experiences related to the management of this condition.MethodsTwo patients with locally advanced and advanced non-squamous non-small cell lung cancer (NSCLC) were enrolled in our hospital. Following the NCCN guidelines and expert consensus, both patients received standard tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The first and second cases reported RCCEP in the skin and anus, among other locations, which were not mentioned in the third case. Furthermore, the resolution of hepatic cavernous hemangiomas in the first and third cases after discontinuing camrelizumab underscores the potential reversibility of these effects, echoing findings from previous research (13,18).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The first and second cases reported RCCEP in the skin and anus, among other locations, which were not mentioned in the third case. Furthermore, the resolution of hepatic cavernous hemangiomas in the first and third cases after discontinuing camrelizumab underscores the potential reversibility of these effects, echoing findings from previous research (13,18).…”
Section: Discussionsupporting
confidence: 80%
“…Prior to this study (13), a solitary article identified just two instances of hepatic hemangioma related to camrelizumab In this study, we present the first account of six patients who developed hepatic hemangiomas after undergoing 5, 16, 12, 14, and 4 cycles of camrelizumab therapy, respectively. In Yonglong Yu's study (13), the number of therapy cycles reported shows similarities to those in our investigation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations